A Single Bout of Fasting (24 h) Reduces Basal Cytokine Expression and Minimally Impacts the Sterile Inflammatory Response in the White Adipose Tissue of Normal Weight F344 Rats. (18th December 2016) - Speaker, Kristin J.; Paton, Madeline M.; Cox, Stewart S.; Fleshner, Monika
Abstract : Sterile inflammation occurs when inflammatory proteins are increased in blood and tissues by nonpathogenic states and is a double-edged sword depending on its cause (stress, injury, or disease), duration (transient versus chronic), and inflammatory milieu. Short-term fasting can exert a host of health benefits through unknown mechanisms. The following experiment tested if a 24 h fast would modulate basal and stress-evoked sterile inflammation in plasma and adipose. Adult male F344 rats were either randomized to ad libitum access to food or fasted for 24 h prior to 0 (control), 10, or 100, 1.5 mA-5 s intermittent, inescapable tail shocks (IS). Glucose, nonesterified free fatty acids (NEFAs), insulin, leptin, and corticosterone were measured in plasma and tumor necrosis factor- (TNF-) α, interleukin- (IL-) 1 β, IL-6, and IL-10 in plasma, and subcutaneous, intraperitoneal, and visceral compartments of white adipose tissue (WAT). In control rats, a 24 h fast reduced all measured basal cytokines in plasma and visceral WAT, IL-1 β and IL-6 in subcutaneous WAT, and IL-6 in intraperitoneal WAT. In stressed rats (IS), fasting reduced visceral WAT TNF- α, subcutaneous WAT IL-1 β, and plasma insulin and leptin. Short-term fasting may thus prove to be a useful dietary strategy for reducing peripheral inflammatory states associated with visceral obesity and chronic stress.